The role of educational policies in the formation of tolerant attitudes and behavior (Journal of Philosophy Culture and Political Science, 2018)
Article is devoted to the role of the tolerance factor in the educational environment. In the article conclusionsabout the ethical, cognitive, humanistic, axiological, social, cultural, communicative potential of the principle oftolerance for education are made. For educational system tolerance is important as a condition of interculturalcommunication, disclosure of the semantic relations in society, the development of moral values, which determinethe nature and impact of social, cultural and spiritual activity of man as a subject of cultural ties and socialrelations. Social tolerance and «methodological» point of view is considered mainly from the standpoint of thepriority of spiritual, ethical component. In the article the authors drew attention to the infl uence of media culture,media technologies and the role of education in the formation of a tolerant environment, tolerant outlook.Key words: tolerance, morals, values, culture, civilization, society, spirituality, communication,education, person, globalization, media-culture